La orientación de la opinión pública de los habitantes de la ciudad de Zumba, cantón Chinchipe, a través de radio San Antonio FM - Peñarreta Rodriguez, Ana Lucia (2015)
All messages are transmitted by means of radio communication manage to persuade people, because the radio is in the window where you can listen and transmit events immediately, which is why this time it was thought important to make a research to find the most remote areas of the province of Zamora Chinchipe, we refer specifically to the city of Zumba, Canton Chinchipe, who express their ideas, views and opinions on matters of public interest. By this context the following problem plated How to design strategies for San Antonio Fm Radio City Zumba, orient the view to enable citizen’s better development of the community? A neat turn, processed and analyzed the data, it was found that within San Antonio Fm, not broadcast opinion programs, this being a limiting factor for the inhabitants of Zumba can express their ideas, thoughts and complaints about the difficulties encountered in the places where they live. This was confirmed at the conclusion and determines that citizens mostly consider relevant implementing a new program of opinion, since the radio can generate opportunities for participation to reach the authorities, informing them of the requirements and criteria citizens. Thus, the information gathered contributed to the alternative approach, which enabled the development of possible solutions regarding the issue, finally an alternative proposal aimed at strengthening public opinion for the citizens of Zumba arises, through a program San Antonio Fm radio. Keywords: media, citizen’s criteria, radio show, audience, communication strategies.